Fodder and seed yields as influenced by row spacing and cutting management of component crops in berseem based intercropping systems - NARWAL, S S; SARDANA, VIRENDER (The Indian Journal of Agricultural Sciences, 2014)
A 2-year field experiment was conducted at Hisar, during the winter season 19"93-94 and 1994-95 to study the influence of component crops on the fodder and seed yield of berseem (Trifolium alexandrinum L). An intercropping of berseem with Brassica crops in different row spacings (100, 150 and 200cm) and cutting management (no cut, 1 cut. 2.cuts) significantly influenced the total green fodder yield. The maximum increase over: sole crop of berseem was registered in berseem + gobhi sarson (Brassica napus L. subsp Oliefera var annua) intercropping system. Among different row spacings, Indian mustard [Brassica juncea L. Czenrj & Cosson] at 100 cm, chinese cabbage (Brassica chinensis L.) at 150 cm and gobhi sarson at 200 em apart rows when intercropped with broadcast sown berseem gave higher fodder yield than other treatments. In berseem + Indian mustard and berseem + gobhi sarson intercropping system, the highest green fodder yield was recorded when sown 100 cm apart and given 2 fodder cuttings. However, in bersecm + chinese cabbage, broadcast sowing resulted in the maximum fodder yield. Sole crop of berseem gave its maximum seed yield. An intercropping of berseem with chinese cabbage or gobhi sarson caused little reduction in its yield compared to sole crop of berseem. Seed yield of berseem in berseem + Indian mustard (broadcast sown) or Indian mustard given 1 or 2 fodder cuttings was significantly higher than Indian mustard sown in wider rows or when left uncut. In berseem + Chinese cabbage intercropping, seed yield of berseem in wider row spacing was significantly higher than its narrow rowspacing or broadcast sowing. The intercropping with Brassica crops decreased their respective yields compared to their sole crop yields. Maximum seed yield of Indian mustard or chinese cabbage Was obtained when grown as. sole crop (uncut). However, seed yield of gobhi sarson eVen after 1 cutting was Similar to that of uncut gobhi sarson.